The Influence of Financial Literacy and Financial Inclusion on Saving and Investment Behaviour for Millennial Generation in DKI Jakarta - Eka Dasra Viana; Budi Purwanto; Alfiana Farah (Universitas Airlangga, 2023)
Background: In 2019, financial literacy level in Indonesia was only 38,03%, while the financial inclusion rate was 76,19%. Financial literacy and inclusion levels related to saving that are identical to the banking sector have the highest values, with 36,12% and 73,88%, while investment in capital market has the second lowest values, at 4,92% and 1,55%. However, the ratio of gross savings to gross domestic product in Indonesia was reported only at 31,01%, while several other Asian countries reached more than 40%. Objective: This study aims to measure the level of financial literacy and inclusion of millennial generations in DKI Jakarta. It analyses the influence of financial literacy and inclusion on saving and investment behaviour, the influence of financial literacy on financial inclusion, and the influence of saving behaviour on investment behaviour. Method: The data analysis used descriptive and SEM-PLS analyses. Results: The results show that the financial literacy rates and the average of inclusion rates of millennial generation in DKI Jakarta are 50% and 60% respectively. Financial literacy and inclusion have an influence on saving and investment behaviour. Also, financial literacy affects financial inclusion, while the saving behaviour does not influence investment behaviour. Conclusion: Financial literacy and inclusion have a positive and significant effect on saving behaviour and investment behaviour. Financial literacy also has a positive and significant effect on financial inclusion. However, saving behaviour does not have a significant effect on investment behaviour. Keywords: financial inclusion; financial literacy; investment behaviour; millennial generation; saving behaviour